2020
DOI: 10.3389/fimmu.2020.01496
|View full text |Cite
|
Sign up to set email alerts
|

IL-34 Actions on FOXP3+ Tregs and CD14+ Monocytes Control Human Graft Rejection

Abstract: Cytokines are major players regulating immune responses toward inflammatory and tolerogenic results. In organ and bone marrow transplantation, new reagents are needed to inhibit tissue destructive mechanisms and eventually induce immune tolerance without overall immunosuppression. IL-34 is a cytokine with no significant homology with any other cytokine but that acts preferentially through CSF-1R, as CSF-1 does, and through PTPζ and CD138. Although IL-34 and CSF-1 share actions, a detailed analysis of their eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 54 publications
3
35
0
Order By: Relevance
“…In rat liver and heart transplantation models, IL‐34 was protective. In a heart transplantation model, we demonstrated that IL‐34 administration differentiates monocytes into regulatory macrophages, which expand and potentiate the suppressive function of CD4 + and CD8 + Tregs, inducing allogeneic tolerance 25,159 . CSF‐1 is also expressed by rat CD8 + Tregs but is not involved in their suppressive function since its blockade did not restore Teff cells proliferation in a suppressive assay, in contrast to IL‐34 blockade 38 .…”
Section: Overlapping and Non‐overlapping Functions Of Il‐34 And Csf‐1 In Diseasesmentioning
confidence: 94%
See 4 more Smart Citations
“…In rat liver and heart transplantation models, IL‐34 was protective. In a heart transplantation model, we demonstrated that IL‐34 administration differentiates monocytes into regulatory macrophages, which expand and potentiate the suppressive function of CD4 + and CD8 + Tregs, inducing allogeneic tolerance 25,159 . CSF‐1 is also expressed by rat CD8 + Tregs but is not involved in their suppressive function since its blockade did not restore Teff cells proliferation in a suppressive assay, in contrast to IL‐34 blockade 38 .…”
Section: Overlapping and Non‐overlapping Functions Of Il‐34 And Csf‐1 In Diseasesmentioning
confidence: 94%
“…CSF‐1 in association with TNFα induces in vitro MDSCs that decrease GVHD severity upon injection 173 . We showed that IL‐34‐macrophages are more efficient to expand Tregs than CSF‐1‐macrophages and those Tregs are highly suppressive as they delay GVHD development in immune humanized NSG mice 25 . In human clinical trials, the protective role of CSF‐1 administration needs to be further investigated because some results showed improved recovery associated with less development of chronic GVHD 174,175 .…”
Section: Overlapping and Non‐overlapping Functions Of Il‐34 And Csf‐1 In Diseasesmentioning
confidence: 96%
See 3 more Smart Citations